Meningkatkan Minat Belajar Anak Slow Learner menggunakan Teknik Token Economy - Dewi, Ratna Monica; Wicaksono, Awang Setiawan (Jurnal Ilmiah Psikomuda (JIPM) Connectedness, 2023)
Each child has their own differences and uniqueness, one of which is how their learning process occurs at school. Some children may immediately understand the lesson, but do not rule out the possibility that there are children who cannot understand the lesson given to them. It can be said that this child is a slow learner. Likewise with children who are Slow Learners. The hope of every inclusive school education is how and what factors are related to the learning process that each student has, one of which is interest in learning. In increasing students' interest in learning, several counseling approaches or techniques are used. One way is by using the token economy technique. The aim of this research is to increase the learning interest of slow learner children using token economy techniques in 6 grade at SDN 13 Gresik. The subjects involved in the research were 3 slow learner children in 6 grade at SDN 13 Gresik. This research uses a quantitative research method with a Pre-Experimental design and a one group pretest-posttest research design. In the results obtained above after carrying out treatment or implementing interventions using the token economy technique, it was found that the score results showed an increase in interest in learning in slow learner children.